Assessing temporal changes in southern right whale foraging ecology and female reproductive cycles - Shuttleworth, Loraine (2022)
Since their international protection in 1935, certain southern right whale (Eubalaena australis; SRWs) populations have been recovering steadily, but they are still far below historical population numbers and are subject to increasing anthropogenic pressures. As capital breeders, the species migrates from offshore summer feeding- to sheltered winter breeding areas. Although population parameters are well studied in some breeding grounds, far less is known about SRW foraging ecology, yet their reproductive success and thus population recovery are largely dependent on foraging success. Based on long-term sighting histories of individually identified females of the South African population of SRWs, the population is estimated to be increasing at an annual rate of 6.5%. However, in the past decade, this population has had an increased rate of reproductive failure, as well as a drastically decreased prevalence on their coastal wintering ground. Furthermore, a northward shift in foraging location has been detected between the 1990s to the 2010s concurrent with a significant decrease in female body condition. Here we aim to use long-term foraging records and endocrine patterns in whale baleen to understand how foraging ecology and reproductive success have co-varied over recent decades. We sub-sampled baleen plates of four females that stranded along the South African coast between 1987 and 2013. Plates were sampled at 2 cm intervals, representing approximately 1-mo sampling intervals. Stable carbon and nitrogen isotopes were used to understand migratory pathways of these four individuals via comparison to known isoscapes, with concurrent reproductive hormone analysis revealing individual pregnancies and inter-calving intervals over approximately decadal timespans for each individual. The working hypothesis is that, concurrent with altered foraging strategies, adult females failed to initiate or maintain gestation, indicative of poor feeding conditions.